Preparation method of moisture-absorbing and quick-drying modified composite filament fabric
By condensing nanotitanium dioxide with intermediate 3 and mixing it with polyester slices and polyacrylonitrile, a moisture absorption and quick-drying modified composite silk fabric was prepared, which solved the problem of insufficient hygroscopicity and antibacterial properties of existing fabrics, and realized the fabric The moisture absorption and rapid drying and antibacterial properties are significantly improved.
Patent Information
- Application Number
- CN202510035138.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing composite silk fabrics have shortcomings in terms of hygroscopicity and antibacterial properties, especially the poor hygroscopicity of polyester fiber fabrics, and the prior art is difficult to improve the moisture permeability and antibacterial properties of the fabric at the same time.
By placing nanotitanium dioxide with intermediate 3 (from 2,2'-diamino-N-methyldiethylamine, 3-bromopropionitrile, 1,4-butanelactone, chloropropyltriethoxysilane and Compounds such as potassium iodide are condensed through a series of reactions to obtain hydrophilic modified nanotitanium dioxide, mixed with polyester slices and polyacrylonitrile, spinning, drafting and textile through a twin-screw high-speed composite spinning machine to prepare wet absorbent Quick-drying modified composite silk fabric.
The prepared modified composite silk fabric not only has good moisture absorption and quick drying effect, but also significantly improves antibacterial properties and can effectively adsorb and kill bacteria. The photocatalytic antibacterial effect of nanotitanium dioxide is synergistic with the electrostatic adsorption effect of quaternary ammonium salt structure. It has achieved a long-term antibacterial effect.
Smart Images

Figure CN119411257A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a method for preparing a moisture-absorbing and quick-drying modified composite silk fabric. Background Art
[0002] Composite silk fabric is a kind of fabric mixed with multiple fibers. It is stronger than single fiber fabric, has good wrinkle resistance and wear resistance, and is widely used in various clothing fields. However, since textiles are most closely related to people's lives, and bacteria and other microorganisms are most likely to come into contact with people through fibers, composite silk fabrics with antibacterial effects are more popular.
[0003] Polyester fiber is the world's most produced synthetic fiber with excellent physical and mechanical properties. However, due to the lack of polar groups in polyester macromolecules and the good structural regularity and high crystallinity of the macromolecular chains, polyester fabrics have poor hygroscopicity and hydrophilicity. Therefore, introducing hydrophilic groups into polyester molecules to improve their hydrophilic and hygroscopic properties has become a hot topic in current research.
[0004] For example, the patent application publication number CN 115519860 A discloses a waterproof and breathable composite fabric and a preparation method thereof. The invention utilizes a large number of carboxyl groups contained in the composite material structure to improve the moisture permeability of the fabric, but does not improve the antibacterial properties of the fabric. Summary of the invention
[0005] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a method for preparing a moisture-absorbing and quick-drying modified composite silk fabric. The prepared composite silk fabric has good antibacterial properties and moisture-absorbing and quick-drying effects.
[0006] (II) Technical solution A method for preparing a moisture-absorbing and quick-drying modified composite silk fabric, the preparation method comprising: (1) Add nano titanium dioxide to deionized water, adjust the pH to 4-5 with 10% hydrochloric acid, add intermediate 3, stir and disperse, heat to 50-60°C, stir and react for 1-2h, centrifuge, wash with deionized water, and dry to obtain hydrophilic modified nano titanium dioxide; (2) The polyester chips, polyacrylonitrile and hydrophilic modified nano titanium dioxide are mixed evenly, spun on a twin-screw high-speed composite spinning machine, balanced for 6-10 hours, oiled and evenly oiled, and then placed on a parallel drawing machine for drawing, re-netting, winding, and finally spinning on a textile machine to obtain a moisture-absorbing and quick-drying modified composite silk fabric.
[0007] Preferably, in (1), the mass of the intermediate 3 is 1-10% of the mass of the nano-titanium dioxide.
[0008] Preferably, in (2), the mass ratio of polyester chips, polyacrylonitrile and hydrophilically modified nano-titanium dioxide is 1:0.8-1.2:0.05-0.2.
[0009] Preferably, in (2), when spinning, the spinning temperature is controlled to be 280°C and the spinning rate is 700 mm / min; when drawing, the temperature of the hot roller is controlled to be 65°C, the setting temperature is 150°C, the drawing rate is 300 m / min, and the drawing multiple is 4.2 times; the network air pressure during re-netting is 5.5 MPa, and the number of networks is 27; the winding speed is 3000 m / min, and when weaving, the yarn feed tension is set to 2.5 cN, the yarn bending depth is 1.0 mm, and the machine speed is 15 r / min.
[0010] Preferably, in (1), the preparation method of intermediate 3 is: S1. Add 2,2'-diamino-N-methyldiethylamine and 3-bromopropionitrile to ethanol solvent, stir and mix evenly, heat to 70-80°C, react for 36-48h, and after the reaction, distill under reduced pressure, wash with ether, and dry to obtain intermediate 1; S2, adding intermediate 1 and 1,4-butane lactone to toluene solvent, stirring and dispersing, heating to 60-70°C, stirring and reacting for 24-36 hours, cooling to room temperature after the reaction, filtering, distilling under reduced pressure, and drying to obtain intermediate 2; S3. Add intermediate 2 and chloropropyltriethoxysilane to N,N-dimethylformamide solvent, stir and disperse, then add potassium iodide, raise the temperature to 90-100°C, stir and react for 24-36 hours. After the reaction is completed, filter, distill under reduced pressure, and dry to obtain intermediate 3.
[0011] More preferably, in S1, the molar ratio of 2,2'-diamino-N-methyldiethylamine to 3-bromopropionitrile is 1:2-2.5.
[0012] Further preferably, in S2, the molar ratio of the intermediate 1 to 1,4-butane lactone is 1:2-2.4.
[0013] Further preferably, in S3, the molar ratio of the intermediate 2 to chloropropyltriethoxysilane is 1:3-4.
[0014] 3. Beneficial technical effects The present invention uses 2,2'-diamino-N-methyldiethylamine and 3-bromopropionitrile as raw materials, obtains intermediate 1 through substitution reaction, and then obtains intermediate 2 through ring-opening reaction with 1,4-butane lactone. The tertiary amine in intermediate 2 and chloropropyltriethoxysilane are subjected to quaternization reaction under the catalysis of potassium iodide to obtain intermediate 3, and then condenses intermediate 3 with hydroxyl groups on the surface of nano titanium dioxide to obtain hydrophilic modified nano titanium dioxide. Finally, polyester chips, polyacrylonitrile and hydrophilic modified nano titanium dioxide are evenly mixed, and through spinning, drawing, weaving and other processes, a moisture-absorbing quick-drying modified composite silk fabric is obtained.
[0015] The modified composite silk fabric prepared by the present invention contains a quaternary ammonium salt structure with a positive charge, which can be adsorbed to the surface of negatively charged bacteria through electrostatic adsorption, destroying the cell membrane, causing the loss of bacterial cell contents, and achieving the purpose of killing bacteria. In addition, the nano titanium dioxide particles contained therein have a photocatalytic antibacterial effect, which can cooperate with the quaternary ammonium salt structure to produce a synergistic antibacterial effect. Introducing it into the modified composite silk fabric can improve the antibacterial performance of the modified composite silk fabric.
[0016] The nano titanium dioxide particles therein not only have a photocatalytic antibacterial effect, but also the titanium dioxide treated organically is evenly dispersed in the fabric and is not easy to migrate out. The present invention combines it with organic matter to introduce carboxylic acid groups and sulfonic acid groups, which can generate hydrogen bonds with water molecules, increase the hydrophilic hygroscopic effect, and introduce it into the fabric to increase the moisture absorption and quick-drying effect of the fabric. The modified composite silk fabric prepared by the present invention has been proven to have good antibacterial effect and moisture absorption and quick-drying effect through experiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is the reaction route for hydrophilic modification of nano-titanium dioxide. DETAILED DESCRIPTION
[0018] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0019] Nano-titanium dioxide, with an average particle size of 25 nm, was obtained from China Pangang Group Titanium Co., Ltd.; Polyester chips and polyacrylonitrile are both from Sinopec Yizheng Chemical Fiber Co., Ltd.
[0020] Example 1
[0021] (1) Add 60 mmol of 2,2'-diamino-N-methyldiethylamine and 150 mmol of 3-bromopropionitrile to ethanol solvent, stir and mix evenly, heat to 75°C, react for 48 hours, and after the reaction is completed, distill under reduced pressure, wash with ether, and dry to obtain intermediate 1. The reaction route is: .
[0022] (2) Add 50 mmol of intermediate 1 and 110 mmol of 1,4-butane lactone to toluene solvent, stir and disperse, heat to 65°C, stir and react for 36 hours. After the reaction is completed, cool to room temperature, filter, vacuum distill and dry to obtain intermediate 2. The reaction route is: .
[0023] (3) Add 20 mmol of intermediate 2 and 60 mmol of chloropropyltriethoxysilane to N,N-dimethylformamide solvent, stir and disperse, then add 8 mmol of potassium iodide, heat to 95°C, stir and react for 36 hours. After the reaction is completed, filter, distill under reduced pressure, and dry to obtain intermediate 3. The reaction route is: .
[0024] (4) Add 10 g of nano titanium dioxide to deionized water, adjust the pH to 4 with 10% hydrochloric acid, then add 0.1 g of intermediate 3, stir and disperse, heat to 50 °C, stir and react for 2 h, centrifuge, wash with deionized water, and dry to obtain hydrophilic modified nano titanium dioxide. The reaction route is: .
[0025] (5) 50 g of polyester chips, 50 g of polyacrylonitrile and 2.5 g of hydrophilic modified nano titanium dioxide were mixed evenly, and spun on a twin-screw high-speed composite spinning machine. The spinning temperature was controlled to be 280 °C, the spinning rate was 700 mm / min, and the spinning was balanced for 10 h. The spinning machine was oiled and oiled, and then placed on a parallel drawing machine for drawing. The temperature of the hot roller was controlled to be 65 °C, the setting temperature was 150 °C, the drawing rate was 300 m / min, and the drawing multiple was 4.2 times. The yarn was re-netted. The net air pressure during re-netting was 5.5 MPa, the number of nets was 27, and the yarn was wound at a speed of 3000 m / min. Finally, the spinning machine was used for weaving. The yarn feed tension was set to 2.5 cN, the yarn bending depth was set to 1.0 mm, and the machine speed was set to 15 r / min to obtain a moisture-absorbing and quick-drying modified composite yarn fabric.
[0026] Example 2
[0027] (1) Add 60 mmol of 2,2'-diamino-N-methyldiethylamine and 140 mmol of 3-bromopropionitrile to ethanol solvent, stir and mix evenly, heat to 80°C, and react for 36 hours. After the reaction is completed, evaporate under reduced pressure, wash with ether, and dry to obtain intermediate 1.
[0028] (2) 50 mmol of intermediate 1 and 115 mmol of 1,4-butane lactone were added to toluene solvent, stirred and dispersed, heated to 65°C, and stirred for reaction for 36 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, vacuum distilled, and dried to obtain intermediate 2.
[0029] (3) Add 20 mmol of intermediate 2 and 70 mmol of chloropropyltriethoxysilane to N,N-dimethylformamide solvent, stir and disperse, then add 6 mmol of potassium iodide, raise the temperature to 95°C, stir and react for 36 hours. After the reaction is completed, filter, distill under reduced pressure, and dry to obtain intermediate 3.
[0030] (4) Add 10 g of nano titanium dioxide into deionized water, adjust the pH to 5 with 10% by mass hydrochloric acid, then add 0.3 g of intermediate 3, stir and disperse, heat to 55 °C, stir and react for 1 h. After completion, centrifuge, wash with deionized water, and dry to obtain hydrophilic modified nano titanium dioxide.
[0031] (5) 50 g of polyester chips, 60 g of polyacrylonitrile and 5 g of hydrophilic modified nano titanium dioxide were mixed evenly, and spun on a twin-screw high-speed composite spinning machine. The spinning temperature was controlled to be 280 °C, the spinning rate was 700 mm / min, and the balance was 8 hours. The spinning machine was oiled and oiled, and then placed on a parallel drawing machine for drawing. The temperature of the hot roller was controlled to be 65 °C, the setting temperature was 150 °C, the drawing rate was 300 m / min, and the drawing multiple was 4.2 times. The net was then re-netted. The net air pressure during re-netting was 5.5 MPa, the number of nets was 27, and the winding was carried out at a speed of 3000 m / min. Finally, the spinning machine was used for weaving. The yarn feeding tension was set to 2.5 cN, the yarn bending depth was set to 1.0 mm, and the machine speed was set to 15 r / min to obtain a moisture-absorbing and quick-drying modified composite silk fabric.
[0032] Example 3
[0033] (1) Add 60 mmol of 2,2'-diamino-N-methyldiethylamine and 120 mmol of 3-bromopropionitrile to ethanol solvent, stir and mix evenly, heat to 70°C, and react for 40 hours. After the reaction is completed, evaporate under reduced pressure, wash with ether, and dry to obtain intermediate 1.
[0034] (2) Add 50 mmol of intermediate 1 and 100 mmol of 1,4-butane lactone into toluene solvent, stir and disperse, heat to 65°C, stir and react for 36 hours. After the reaction is completed, cool to room temperature, filter, evaporate under reduced pressure, and dry to obtain intermediate 2.
[0035] (3) Add 20 mmol of intermediate 2 and 65 mmol of chloropropyltriethoxysilane to N,N-dimethylformamide solvent, stir and disperse, then add 8 mmol of potassium iodide, raise the temperature to 100°C, stir and react for 26 hours. After the reaction is completed, filter, distill under reduced pressure, and dry to obtain intermediate 3.
[0036] (4) Add 10 g of nano titanium dioxide into deionized water, adjust the pH to 4 with 10% hydrochloric acid, add 0.5 g of intermediate 3, stir and disperse, heat to 60 °C, stir and react for 2 h. After completion, centrifuge, wash with deionized water, and dry to obtain hydrophilic modified nano titanium dioxide.
[0037] (5) 50 g of polyester chips, 40 g of polyacrylonitrile and 6 g of hydrophilic modified nano titanium dioxide were mixed evenly, and spun on a twin-screw high-speed composite spinning machine. The spinning temperature was controlled to be 280 °C, the spinning rate was 700 mm / min, and the spinning was balanced for 6 hours. The spinning machine was oiled and oiled, and then the spinning machine was placed on a parallel drawing machine for drawing. The hot roller temperature was controlled to be 65 °C, the setting temperature was 150 °C, the drawing rate was 300 m / min, and the drawing multiple was 4.2 times. The spinning machine was re-netted. The network air pressure during re-netting was 5.5 MPa, the network number was 27, and the spinning machine was wound at a speed of 3000 m / min. Finally, the spinning machine was used for weaving. The yarn feeding tension was set to 2.5 cN, the yarn bending depth was set to 1.0 mm, and the machine speed was set to 15 r / min to obtain a moisture-absorbing and quick-drying modified composite silk fabric.
[0038] Example 4
[0039] (1) Add 60 mmol of 2,2'-diamino-N-methyldiethylamine and 140 mmol of 3-bromopropionitrile to ethanol solvent, stir and mix evenly, heat to 75°C, react for 48 hours. After the reaction is completed, distill under reduced pressure, wash with ether, and dry to obtain intermediate 1.
[0040] (2) Add 50 mmol of intermediate 1 and 120 mmol of 1,4-butane lactone into toluene solvent, stir and disperse, heat to 60°C, stir and react for 36 hours. After the reaction is completed, cool to room temperature, filter, vacuum distill and dry to obtain intermediate 2.
[0041] (3) Add 20 mmol of intermediate 2 and 80 mmol of chloropropyltriethoxysilane to N,N-dimethylformamide solvent, stir and disperse, then add 6 mmol of potassium iodide, raise the temperature to 90°C, stir and react for 36 hours. After the reaction is completed, filter, distill under reduced pressure, and dry to obtain intermediate 3.
[0042] (4) Add 10 g of nano titanium dioxide into deionized water, adjust the pH to 4 with 10% hydrochloric acid, add 0.7 g of intermediate 3, stir and disperse, heat to 55 °C, stir and react for 2 h. After completion, centrifuge, wash with deionized water, and dry to obtain hydrophilic modified nano titanium dioxide.
[0043] (5) 50 g of polyester chips, 45 g of polyacrylonitrile and 8 g of hydrophilic modified nano titanium dioxide were mixed evenly, and spun on a twin-screw high-speed composite spinning machine. The spinning temperature was controlled to be 280 °C, the spinning rate was 700 mm / min, and the balance was 8 hours. The spinning machine was oiled and oiled, and then placed on a parallel drawing machine for drawing. The temperature of the hot roller was controlled to be 65 °C, the setting temperature was 150 °C, the drawing rate was 300 m / min, and the drawing multiple was 4.2 times. The net was then re-netted. The net air pressure during re-netting was 5.5 MPa, the number of nets was 27, and the winding was carried out at a speed of 3000 m / min. Finally, the spinning machine was used for weaving. The yarn feeding tension was set to 2.5 cN, the yarn bending depth was set to 1.0 mm, and the machine speed was set to 15 r / min to obtain a moisture-absorbing and quick-drying modified composite silk fabric.
[0044] Example 5
[0045] (1) Add 60 mmol of 2,2'-diamino-N-methyldiethylamine and 130 mmol of 3-bromopropionitrile to ethanol solvent, stir and mix evenly, heat to 75°C, and react for 40 hours. After the reaction is completed, evaporate under reduced pressure, wash with ether, and dry to obtain intermediate 1.
[0046] (2) Add 50 mmol of intermediate 1 and 110 mmol of 1,4-butane lactone into toluene solvent, stir and disperse, heat to 70°C, stir and react for 24 hours. After the reaction is completed, cool to room temperature, filter, evaporate under reduced pressure, and dry to obtain intermediate 2.
[0047] (3) Add 20 mmol of intermediate 2 and 75 mmol of chloropropyltriethoxysilane to N,N-dimethylformamide solvent, stir and disperse, then add 5 mmol of potassium iodide, raise the temperature to 95°C, stir and react for 24 hours. After the reaction is completed, filter, distill under reduced pressure, and dry to obtain intermediate 3.
[0048] (4) Add 10 g of nano titanium dioxide into deionized water, adjust the pH to 4 with 10% hydrochloric acid, then add 1 g of intermediate 3, stir and disperse, heat to 55 °C, stir and react for 1 h. After completion, centrifuge, wash with deionized water, and dry to obtain hydrophilic modified nano titanium dioxide.
[0049] (5) 50 g of polyester chips, 50 g of polyacrylonitrile and 10 g of hydrophilic modified nano titanium dioxide were mixed evenly, and spun on a twin-screw high-speed composite spinning machine. The spinning temperature was controlled to be 280 °C, the spinning rate was 700 mm / min, and the spinning was balanced for 10 hours. The spinning machine was oiled and oiled, and then the spinning machine was placed on a parallel drawing machine for drawing. The hot roller temperature was controlled to be 65 °C, the setting temperature was 150 °C, the drawing rate was 300 m / min, and the drawing multiple was 4.2 times. The spinning machine was re-netted. The network air pressure during re-netting was 5.5 MPa, the network number was 27, and the spinning machine was wound at a speed of 3000 m / min. Finally, the spinning machine was used for weaving. The yarn feeding tension was set to 2.5 cN, the yarn bending depth was set to 1.0 mm, and the machine speed was set to 15 r / min to obtain a moisture-absorbing and quick-drying modified composite silk fabric.
[0050] Comparative Example 1 The difference between this comparative example and Example 1 is that nano titanium dioxide is used in step (5) instead of hydrophilic modified nano titanium dioxide.
[0051] Refer to GB / T21655.1-2023 to test the moisture absorption and quick-drying performance.
[0052] Table 1:
[0053] It can be seen from the table that the water absorption rates of Examples 1-5 are all greater than 200% of the standard value, the moisture permeabilities are all greater than 10000 of the standard value, the evaporation rates are all greater than 0.18 of the standard value, and the water absorption rates, moisture permeabilities and evaporation rates are all greater than those of Comparative Example 1. Therefore, the composite silk fabrics prepared by the present invention have good moisture absorption and quick-drying effects.
[0054] Refer to FZ / T73023-2006 to test the antibacterial properties.
[0055] Table 2:
[0056] It can be seen from the table that the modified composite silk fabric prepared by the present invention has a good antibacterial effect, and the quaternary ammonium salt structure and nano titanium dioxide have a better synergistic antibacterial effect. After being washed 50 times, it still has a good antibacterial effect. This is because the unmodified nano titanium dioxide is easy to agglomerate in the fabric, has poor compatibility with organic substances, and is easy to migrate out, while the modified nano titanium dioxide can be evenly dispersed in the fabric, and the unreacted Si-O bonds can be condensed with the hydroxyl groups on the surface of the fabric fiber, further improving the adhesion of the nano titanium dioxide in the fabric, and achieving a good long-term antibacterial effect.
[0057] The above-mentioned specific implementation examples are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a moisture-absorbing and quick-drying modified composite silk fabric, characterized in that: The preparation method is: (1) Add nano titanium dioxide to deionized water, adjust the pH to 4-5 with 10% hydrochloric acid, add intermediate 3, stir and disperse, heat to 50-60°C, stir and react for 1-2h, centrifuge, wash with deionized water, and dry to obtain hydrophilic modified nano titanium dioxide; (2) The polyester chips, polyacrylonitrile and hydrophilic modified nano titanium dioxide are mixed evenly, spun on a twin-screw high-speed composite spinning machine, balanced for 6-10 hours, oiled and evenly oiled, then placed on a parallel drafting machine for drafting, re-netted, wound, and finally spun on a textile machine to obtain a moisture-absorbing and quick-drying modified composite silk fabric; The preparation method of the intermediate 3 is: S1. Add 2,2'-diamino-N-methyldiethylamine and 3-bromopropionitrile to ethanol solvent, stir and mix evenly, heat to 70-80°C, react for 36-48h, and after the reaction, distill under reduced pressure, wash with ether, and dry to obtain intermediate 1, whose structural formula is ; S2, adding intermediate 1 and 1,4-butane lactone to toluene solvent, stirring and dispersing, heating to 60-70°C, stirring and reacting for 24-36 hours, cooling to room temperature after the reaction, suction filtering, vacuum distillation, and drying to obtain intermediate 2, whose structural formula is ; S3, adding intermediate 2 and chloropropyltriethoxysilane to N,N-dimethylformamide solvent, stirring and dispersing, adding potassium iodide thereto, heating to 90-100°C, stirring and reacting for 24-36 hours, filtering after the reaction, distilling under reduced pressure, and drying to obtain intermediate 3, whose structural formula is .
2. The method for preparing the moisture-absorbing and quick-drying modified composite silk fabric according to claim 1, characterized in that: In the above (1), the mass of the intermediate 3 is 1-10% of the mass of the nano-titanium dioxide.
3. The method for preparing the moisture-absorbing and quick-drying modified composite silk fabric according to claim 1, characterized in that: In the above (2), the mass ratio of polyester chips, polyacrylonitrile and hydrophilic modified nano-titanium dioxide is 1:0.8-1.2:0.05-0.
2.
4. The method for preparing the moisture-absorbing and quick-drying modified composite silk fabric according to claim 1, characterized in that: In the above (2), when spinning, the spinning temperature is controlled to be 280°C and the spinning rate is 700 mm / min; when drawing, the temperature of the hot roller is controlled to be 65°C, the setting temperature is 150°C, the drawing rate is 300 m / min, and the drawing multiple is 4.2 times; the network air pressure during re-netting is 5.5 MPa, and the number of networks is 27; the winding speed is 3000 m / min, and when weaving, the yarn feeding tension is set to 2.5 cN, the yarn bending depth is 1.0 mm, and the machine speed is 15 r / min.
5. The method for preparing the moisture-absorbing and quick-drying modified composite silk fabric according to claim 1, characterized in that: In the S1, the molar ratio of 2,2'-diamino-N-methyldiethylamine to 3-bromopropionitrile is 1:2-2.
5.
6. The method for preparing the moisture-absorbing and quick-drying modified composite silk fabric according to claim 1, characterized in that: In the S2, the molar ratio of the intermediate 1 to 1,4-butane lactone is 1:2-2.
4.
7. The method for preparing the moisture-absorbing and quick-drying modified composite silk fabric according to claim 1, characterized in that: In S3, the molar ratio of the intermediate 2 to chloropropyltriethoxysilane is 1:3-4.
Citation Information
Patent Citations
Waterproof moisture-permeable composite fabric and preparation method thereof
CN115519860A
Cited By
Preparation method of anti-ultraviolet modified polyester fabric
CN120006527A